PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, STRUKTUR KEPEMILIKAN INSTITUSIONAL, SET KESEMPATAN INVESTASI, UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Purwo Adi Nugroho (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2017)
The main purpose of this study was to determine the effect of managerial ownership structure, institutional ownership structure, investment opportunity set and firm size on firm value. The population of this study is a real estate company that listed on the Indonesia Stock Exchange with the observation period 2008 to 2012. Data obtained by the method of purposive sampling and the 42 companies sampled each year. The method of analysis used is multiple linear regression by using SPSS 20.0. The results of this study indicate that: (1) managerial ownership structure has no effect on firm value, (2) institutional ownership structure has significant effect on firm value, (3) investment opportunity set has significant effect on firm value, and (4) firm size has significant effect on firm value.